Constructing heterojunction interface of Co3O4/TiO2 for efficiently accelerating acetaminophen degradation via photocatalytic activation of sulfite - Qiangwei Li; Mengmeng Zhang; Yongyi Xu; Xiaoqi Quan; Yiao Xu; Liu, Wen; Lidong Wang (Chinese Chemical Letters, 2023)
Achieving efficient degradation of organic pollutants via activation of sulfite is meaningful but challenging. Herein, we have constructed a heterogeneous catalyst system involving Co3O4 and TiO2 nanoparticles to form the p-n heterojunction (Co3O4/TiO2) to degrade acetaminophen (ACE) through photocatalytic activation of sulfite. Specifically, X-ray photoelectron spectroscopy analysis and theoretical calculations provide compelling evidence of electron transfer from Co3O4 to TiO2 at the heterointerface. The interfacial electron redistribution of Co3O4/TiO2 tunes the adsorption energy of HSO3‒/SO32‒ in sulfite activation process for enhanced the catalytic activity. Owing to its unique heterointerface, the degradation efficiency of ACE reached 96.78% within 10 min. The predominant active radicals were identified as •OH, h+, and SOx•− through radical quenching experiments and electron spin resonance capture. Besides, the possible degradation pathway was deduced by monitoring the generated intermediate products. Thereafter, the enhanced roles of well-engineered compositing interface in photocatalytic activation of sulfite for complete degradation of ACE were unveiled that it can improve light absorption ability, facilitate the generation of active species, and optimize reactive pathways. Considering that sulfite is a waste from flue gas desulfurization process, the photocatalytic activation of sulfite system will open up new avenues of beneficial use of air pollutants for the removal of pharmaceutical wastewater.
Keywords: Charge transfer; Degradation mechanism; Heterojunction interface; Photocatalytic activation; Sulfite